New Image Pattern & Decoration : From the Morton G. Neumann Family Collection - Madison Art Center, Madison; David Alfred Smart Gallery of the University of Chicago; Flint Institute of Arts, Flint; Arkansas Art Center, Little Rock; Memorial Art Gallery of the University of Rochester (Kalamazoo : Kalamazoo Institute fo Arts, 1983)
Africano, Nicolas ; Ahearn, John ; Basquiat, Jean-Michel ; borofsky, Jon ; Bosman, Richard ; Chase, Louisa ; Chia, Sandro ; Clemente, Francesco ; Combas, Robert ; Cutrone, Ronnie ; Fetting, Rainer ; Garet, Jedd ; Haring, Keith ; Penck, A.R. ; Salle, David ; Salomé ; Scharf, Kenny ; Schnabel, Julian ; Signler, Hollis ; sullivan, James ; Zucker, Joe ; Jaudon, Valerie ; Kalina, Richard ; Kozloff, Joyce ; Kushner, Robert ; Mac Connel, Kim ; Ripps, Rodney ; Samaras, Lucas ; Schpiro, Miriam ; Schwartz, Barbara ; Zakanitch, Robert
New Image Pattern & Decoration : From the Morton G. Neumann Family Collection. An Exhibition organized and circulated by Kalamazoo Institute of Arts, March 18, 1983 - May 1, 1983 ; Madison Art Center, Madison, August 1, 1983 - September 18, 1983 ; David Alfred Smart Gallery of the University of Chicago , October 5, 1983 - December 4, 1983 ; Flint Institute of Arts, Flint, April 23, 1984 - June 3, 1984 ; Arkansas Art Center, Little Rock, August 27, 1984 - October 7, 1984 ; Memorial Art Gallery of the University of Rochester, October 26, 1984 - November 25, 1984
boek